Laryngotracheal stenosis in critically ill patients - Lukáš, Jindřich; Votruba, Jiří; Paska, Jan; Cernohorský, Stanislav; Lukáš, David; Machoň, Vladimír (Acta oto-laryngologica, 2011)
CONCLUSIONS: Prolonged artificial pulmonary ventilation by tracheostomy tube (>30 days) doubled the risk of stenosis (relative risk, RR = 2.04, p = 0.002). Critically ill patients with repeated tracheotomies were more than six times likely to experience stenosis (RR = 6.44, p< 0.001) than other critically ill patients. OBJECTIVE: In this retrospective study, we describe the occurrence of laryngotracheal stenosis (LTS) in critically ill patients after elective tracheostomy who had undergone treatment for LTS at the Na Homolce Hospital in Prague, Czech Republic. METHODS: We studied 28 patients who were diagnosed with symptomatic LTS. Basic major demographic data, duration of mechanical ventilation, onset of tracheal stenosis after decannulation, and tracheostomy type (percutaneous dilatational or surgical tracheostomy) were recorded. The number of patients requiring repeated tracheostomies was also recorded. RESULTS: Neither the demographic data nor the type of tracheostomy represented statistically significant risk factors. The risk factors for LTS were prolonged artificial pulmonary ventilation using the tracheostomy tube (p = 0.005) and repeated tracheostomy (p< 0.001). The mean onset of stenosis symptoms was 53.7 days (range 2-300 days), with a median of 58 days. Stenosis involved the trachea in 20 patients, subglottis in five cases, and glottis and subglottis in three cases. Seven patients (25%) underwent a tracheal resection and primary end-to-end reconstruction. One patient underwent laryngotracheoplasty with dilatation. The procedure was endoscopic in 18 patients (64.3%). Two patients (7.1%) received permanent tracheostomies.
Keywords: senioři; umělé dýchání; Intensive Care Units; reoperace; tracheostomie; Male; Retrospective Studies; bronchoskopie; Middle Aged; mužské pohlaví; Tracheostomy; Reoperation; Follow-Up Studies; Tracheal Stenosis; následné studie; ženské pohlaví; odpojení od ventilátoru; retrospektivní studie; Humans; kritický stav; laryngostenóza; jednotky intenzivní péče; Bronchoscopy; stenóza průdušnice; lidé středního věku; rizikové faktory; Female; Aged; Risk Factors; Ventilator Weaning; Critical Illness; lidé; Laryngostenosis; Respiration, Artificial